The Usability Engineering of a Voice-Controlled Answering Machine - Gamm, Stephan; Haeb-Umbach, Reinhold; Langmann, Det (International Symposium on Human Factors in Telecommunications, Melbourne)

Speech recognition algorithms for voice control interfaces - Haeb-Umbach, Reinhold; Beyerlein, Peter; Geller, Dieter (Philips Journal of Research)
Recognition accuracy has been the primary objective of most speech recognition research, and impressive results have been obtained, e.g. less than 0.3% word error rate on a speaker-independent digit recognition task. When it comes to real-world applications, robustness and real-time response might be more important issues. For the first requirement we review some of the work on robustness and discuss one specific technique, spectral normalization, in more detail. The requirement of real-time response has to be considered in the light of the limited hardware resources in voice control applications, which are due to the tight cost constraints. In this paper we discuss in detail one specific means to reduce the processing and memory demands: a clustering technique applied at various levels within the acoustic modelling.

Automatic Transcription of Unknown Words in a Speech Recognition System - Haeb-Umbach, Reinhold; Beyerlein, P.; Thelen, E. (ICASSP, Detroit)
We address the problem of automatically finding an acoustic representation (i.e. a transcription) of unknown words as a sequence of subword units, given a few sample utterances of the unknown words, and an inventory of speaker-independent subword units. The problem arises if a user wants to add his own vocabulary to a speaker-independent recognition system simply by speaking the words a few times. Two methods are investigated which are both based on a maximum-likelihood formulation of the problem. The experimental results show that both automatic transcription methods provide a good estimate of the acoustic models of unknown words. The recognition error rates obtained with such models in a speaker-independent recognition task are clearly better than those resulting from separate whole-word models. They are comparable with the performance of transcriptions drawn from a dictionary.

The Philips Research system for continuous-speech dictation - Steinbiss, Volker; Ney, Hermann J.; Aubert, Xavier L.; Besling, Stefan; Dugast, Christian; Essen, Ute; Geller, Dieter; Haeb-Umbach, Reinhold; Kneser, Reinhard; Meier, Hans Günter; Oerder, Martin; Tran, Bach Hiep (Philips Journal of Research)
This paper gives an overview of the Philips Research system for continuous-speech recognition. The recognition architecture is based on an integrated statistical approach. The system has been successfully applied to various tasks in American English and German, ranging from small vocabulary tasks to very large vocabulary tasks and from recognition only to speech understanding. Here, we concentrate on phoneme-based continuous-speech recognition for large vocabulary recognition as used for dictation, which covers a significant part of our research work on speech recognition. We describe this task and report on experimental results. In order to allow a comparison with the performance of other systems, a section with an evaluation on the standard North American Business news (NAB2) task (dictation of American English newspaper text) is supplied.

Continuous speech dictation - From theory to practice - Steinbiss, Volker; Ney, Hermann J.; Essen, Ute; Tran, Bach Hiep; Aubert, Xavier L.; Dugast, Christian; Kneser, Reinhard; Meier, Hans Günter; Oerder, Martin; Haeb-Umbach, Reinhold; Geller, Dieter; Hoellerbauer, W.; et al. (Speech Communication)
This paper gives an overview of the Philips research system for phoneme-based, large-vocabulary, continuousspeech recognition. The system has been successfully applied to various tasks in the German and (American) English languages, ranging from small vocabulary tasks to very large vocabulary tasks. Here, we concentrate on continuousspeech recognition for dictation in real applications, the dictation of legal reports and radiology reports in German. We describe this task and report on experimental results. We also describe a commercial PC-based dictation system which includes a PC implementation of our scientific recognition prototype. In order to allow for a comparison with the performance of other systems, a section with an evaluation on the standard Wall Street Journal task (dictation of American English newspaper text) is supplied. The recognition architecture is based on an integrated statistical approach. We describe the characteristic features of the system as opposed to other systems: 1. the Viterbi criterion is consistently applied both in training and testing; 2. continuous mixture densities are used without tying or smoothing; 3. time-synchronous beam search in connection with a phoneme look-ahead is applied to a tree-organized lexicon.

Synthesis Procedures for Self-Testable Controllers - Hellebrand, Sybille; Wunderlich, Hans-Joachim

Evaluation of Self-Testable Controller Architectures Based on Realistic Fault Analysis - Hellebrand, Sybille; Wunderlich, Hans-Joachim; Goncalves, F.; Paulo Teixeira, Joao

Partitioning of CMOS-Circuits for On-Chip IDDQ-Testing - Hellebrand, Sybille; Herzog, Maik; Wunderlich, Hans-Joachim

Pattern Generation for a Deterministic BIST Scheme - Hellebrand, Sybille; Reeb, Birgit; Tarnick, Steffen; Wunderlich, Hans-Joachim
Keywords: WORKSHOP

Quasi-particle band structure of C(111)2 × 1 and C(100)2 × 1 surfaces - Kress, Clemens; Fiedler, Marion; Schmidt, Wolf Gero; Bechstedt, Friedhelm (Surface Science)

III-V(110)/Sb(1 ML): structural and dynamical properties - Schmidt, Wolf Gero; Srivastava, G.P. (Surface Science)

Torque capability and control of a saturated induction motor over a wide range of flux weakening - Grotstollen, H.; Wiesing, J. (IEEE Transactions on Industrial Electronics)
Keywords: Electrical and Electronic Engineering; Control and Systems Engineering

Computer aided design and modeling of high frequency magnetic components - Becker, B.; Grotstollen, H.; Heinemann, L. (Proceedings of 1995 IEEE Applied Power Electronics Conference and Exposition - APEC'95)

Simulation of power electronic circuits with principles used in wave digital filters - Fiedler, A.; Grotstollen, H. (IAS '95. Conference Record of the 1995 IEEE Industry Applications Conference Thirtieth IAS Annual Meeting)

Investigation of asymmetrical phase-shifted full bridge [power convertors] - Fiedler, A.; Grotstollen, H. (Proceedings of IECON '95 - 21st Annual Conference on IEEE Industrial Electronics)

Simulation model for ultrasonic motors powered by resonant converters - Maas, Jürgen; Ide, Peter; Fröhleke, Norbert; Grotstollen, Horst (IAS '95. Conference Record of the 1995 IEEE Industry Applications Conference Thirtieth IAS Annual Meeting)

Investigation of PWM controlled, resonant transition converters with asymmetrical duty cycle - Fröhleke, Norbert; Fiedler, A.; Grotstollen, Horst; Margaritis, Basile (Proceedings of IECON '95 - 21st Annual Conference on IEEE Industrial Electronics)

Optimal pulsewidth modulation techniques for high-power voltage-source inverter - Sun, Jian

A Systematic Approach to State Feedback Controller Design for DC/DC Line-Side Traction Converters - Böcker, Joachim; Endrikat, Christian; Liu, Steven (EPE’95, Sevilla)

Netzkupplungsumrichter Jübek – Regelung - Janning, Jörg; Böcker, Joachim; Anbuhl, Kay; Boni, Marco (Elektrische Bahnen)

Built-In Test for Circuits with Scan Based on Reseeding of Multiple-Polynomial Linear Feedback Shift Registers - Hellebrand, Sybille; Rajski, Janusz; Tarnick, Steffen; Venkataraman, Srikanth; Courtois, B. (IEEE Transactions on Computers)

Pattern Generation for a Deterministic BIST Scheme - Hellebrand, Sybille; Reeb, Birgit; Tarnick, Steffen; Wunderlich, Hans-Joachim (ACM/IEEE International Conference on Computer Aided Design (ICCAD'95))

́Ich wäre gerne ein Engel ́. Zu Peter Roos' Demaskerade seines als Kunstwerk verkleideten Geschlechtskörpers - Öhlschläger, Claudia; Bettinger, Elfi (Maskeraden. Geschlechterdifferenz in der literarischen Inszenierung)

Rezension zu Susanne Lummerding: "Weibliche" Ästhetik? Möglichkeiten und Grenzen einer Subversion von Codes. Wien: Passagen 1994 - Öhlschläger, Claudia (Rundbrief Frauen in der Literaturwissenschaft 44: Zensur. Mai 1995)

SINGLE-STAGE AND DOUBLE-STAGE ACOUSTOOPTICAL TI-LINBO3 TE-TM CONVERTERS USED IN WAVELENGTH-SELECTIVE POLARIMETER AND POLARIZATION-INDEPENDENT DEPOLARIZER - REHAGE, M; Noé, Reinhold; HARIZI, C; RICKEN, R (FIBER OPTIC NETWORK COMPONENTS)

Weibliche" Ästhetik? Möglichkeiten und Grenzen einer Subversion von Codes - Öhlschläger, Claudia (Rundbrief Frauen in der Literaturwissenschaft)

MULTISTAGE SPECTRAL POLARIMETER WITH GREATER-THAN-28DB STOPBAND ATTENUATION - Noé, Reinhold; REHAGE, M; TIAN, F (ELECTRONICS LETTERS)

Conjugated Polymers for CMOS Compatible Applications - Muller, J.; Mankowski, V.; Hilleringmann, Ulrich; Goser, K.; Holmes, A.; Gelsen, O.; Stern, R. (ESSDERC ’95: Proceedings of the 25th European Solid State Device Research Conference)

Quantum beats from biexcitons in narrow quantum wells: polarization and density dependence - Meier, Torsten; Albrecht, T.F.; Schulze, A.; Koch, M.; Bott, K.; Feldmann, J.; Stolz, W.; Kuhl, J.; Mayer, E.J.; Koch, S.W.; Göbel, E.O.; Cundiff, S.T. (Quantum Electronics and Laser Science Conference)
Transient four-wave mixing (TFWM) has been extensively used during the last few years to study exciton dynamics in semiconductors and in semiconductor heterostructures. These studies have provided significant insight into exciton dynamics in both ordered and disordered systems. There are, nevertheless, still certain aspects of the excitonic TFWM response that are not completely understood. In particular, a complete understanding of the polarization and intensity dependences of the signai strength, the decay of the time-integrated signal, and the temporal characteristics of the time-resolved signal has proven elusive. Recent theoretical and experimental work has indicated that exciton-exciton interactions are important.1·2 Such interactions include incoherent processes, such as excitation-induced dephasing, and the formation of biexcitons. Additionally, some of the phenomena result from disorder, making them sample dependent.

Polarization dependence of quantum beats between light-hole and heavy-hole excitons in GaAs quantum wells - Meier, Torsten; Kuhl, J.; Mayer, E.J.; Smith, G.O.; Bott, K.; Heuckeroth, V.; Thomas, P.; Koch, M.; Hey, R.; Ploog, K. (Quantum Electronics and Laser Science Conference)
The appearance of quantum beats (QBs) between heavy-hole (hh) and light-hole (lh) excitons in GaAs quantum wells (QWs) has been observed in many degenerate-four- wave-mixing (DFWM) experiments with subpicosecond optical pulses. Although the variation of the beat amplitude and phase with polarization of the incident pulses was recognized early on, a consistent theoretical interpretation of exciton coherence for the case of simultaneous excitation of hh and lh excitons is still missing.

Weak Sequential Composition in Process Algebras - Rensink, Arend; Wehrheim, Heike (CONCUR '94, Concurrency Theory, 5th International Conference, Uppsala, Sweden, August 22-25, 1994, Proceedings)

Aussagenlogik - Deduktion und Algorithmen - Kleine Büning, Hans; Lettmann, Theodor

Hilbert’s Axiomatic Programme and Philosophy - Peckhaus, Volker (The History of Modern Mathematics, Bd. 3: Images, Ideas, and Communities)
Rezensionen: MR 95c:01028 (R. Murawski); Zbl. Math. 806.01018 (J.J. Burkhardt).

Der deutsche Roman 1815-1830. Bibliographie. Standortverzeichnisse, Rezensionen, Forschungsüberblick - Eke, Norbert Otto; Olasz-Eke, Dagmar

Geschichten aus (der) Geschichte. Zum Stand des historischen Erzählens im Deutschland der frühen Restaurationszeit

Heiner Müller - Eke, Norbert Otto (Deutsche Dichter des 20. Jahrhunderts)

„Lieber Niembsch“ oder: Der Dichter im Gehäus. Anmerkungen zu Manfred Karges Spiel mit Biographie und Geschichte um den Autor im „Stadium der Verrücktheit“ - Eke, Norbert Otto (Lenau-Forum)

Vergangene Zeiten. Anmerkungen zur Semantik des Umbruchs und zu den Bedeutungsstrukturen im historischen Erzählen der frühen Restaurationszeit (1815-1830) - Eke, Norbert Otto (Geschichten aus (der) Geschichte. Zum Stand des historischen Erzählens im Deutschland der frühen Restaurationszeit)

Der historische Roman der frühen Restaurationszeit. Zur Einführung - Eke, Norbert Otto; Steinecke, Hartmut (Geschichten aus (der) Geschichte. Zum Stand des historischen Erzählens im Deutschland der frühen Restaurationszeit)

Graph Gramars and Their Application to Computer Science, 5th International Workshop (1994), Selected Papers

Berücksichtigung von Datenschutzaspekten in einem bevölkerungsbezogenen Krebsregister - Thoben, Wilfried; Appelrath, Hans-Jürgen; Rettig, Jens; Sauer, Stefan (Proceedings of the conference on Medizin und Information, Biometrie und Epidemiologie (GMDS 1994), Dresden (Germany))
Die Pilotphase 1993/ 94 zum Aufbau eines Niedersächsischen Krebsregister untersucht das im Entwurf des Bundeskrebsregistergesetzes vorgesehen Modell für ein bevölkerungsbezogenes Krebsregister. Darin werden die Krebsmeldungen in einer Vertrauensstelle erfaßt und die personenidentifizierenden Daten vor der Übermittlung an die Registerstelle anonymisiert, wo sie dann zu einem bevölkerungsbezogenen Krebsregister verdichtet und epidemiologischer Forschung zur Verfügung gestellt werden ([1], [2], [3]). Dieses sogenannte „Michaelis“-Modell erlaubt eine bevölkerungsbezogene Registrierung von Krebsfällen unter Berücksichtigung datenschutzrechtlicher Aspekte („Informationelles Selbstbestimmungsrecht“) der einzelnen Betroffenen. In vier Teilprojekten werden dabei in der Modellregion Weser-Ems die Integration krebsregistrierender Einrichtungen, die Chiffrierung/ Dechiffrierung von Krebsmeldungen, der Abgleich anonymisierter Meldungen in der Registerstelle und die Entwicklung eines epidemiologischen Informationssystem betrachtet ([4], [5]).

Optical Modelling, Simulation and Improvement of PV Module Encapsulation - Krauter, Stefan; Hanitsch, Rolf; Campbell, P.; Wenham, S.R. (Proceedings of the 12th European Photovoltaic Solar Energy Conference, Amsterdam (Niederlande), 11.–15. April 1994, Band 2, S. 1198–1201)

Simulation Tool for Prediction and Optimization of Output Power Considering Thermal and Optical Parameters of PV Module Encapsulation - Strauss, Philipp; Onneken, K.; Krauter, Stefan; Hanitsch, Rolf (Proceedings of the 12th European Photovoltaic Solar Energy Conference, Amsterdam (Niederlande), 11.–15. April 1994, Band 2, S. 1194–1197.)

Einfluß optischer und thermischer Parameter auf den Tageswirkungsgrad von photovoltaischen Modulen - Krauter, Stefan; Hanitsch, Rolf (Neuntes Internationales Sonnenforum, Berlin (Deutschland), 28. Juni – 1. Juli 1994, S. 495–502)

Simulation of Thermal and Optical Performance of PV Modules - Krauter, Stefan; Hanitsch, Rolf; Wenham, S. R. (Proceedings of the 3rd World Renewable Energy Congress, Reading (UK), 11.–16. September 1994)

Actual Optical and Thermal Performance of PV-Modules - Krauter, Stefan (Proceedings of the 1st World Conference on Photovoltaic Energy Conversion (Joint Congress of IEEE/PVSEC/EUPVSEC), Waikoloa, Hawaii (USA), 5.–9. Dezember 1994, S. 734–737.)

Syntax and Semantics of Hybrid Database Languages - Andries, Marc; Engels, Gregor (Proceedings of the International Workshop on Graph Transformations in Computer Science (1993), Dagstuhl (Germany))
We present the hybrid query language HQL/EER for an Extended Entity-Relationship model. As its main characteristic, this language allows a user to freely mix graphical and textual formulation of a query. We show how syntax and semantics of this hybrid language are formally defined by means of a slightly extended version of PROGRES, a specification formalism based on programmed and attributed graph rewriting systems.

Specification of coordinated behaviour by SOCCA - Engels, Gregor; Groenewegen, Luuk (Proceedings of the Third European Workshop on Software Process Technology (EWSPT 1994), Villard de Lans (France))

Windatlas für das PESAG-Versorgungsgebiet - Bendfeld, Jörg; Ernst, Achim; Ortjohann, Egon

Flächendeckende Windpotentialbestimmung in einer Binnenlandregion mit ausgeprägter Orographie - Bendfeld, Jörg; Ernst, Achim; Ortjohann, Egon; Langrock, Beate; Scholz, Norbert (Renergie 94 - Windenergienutzung im Binnenland, Solarenergienutzung in Deutschland)

Improvements in beam search for 10000-word continuous-speech recognition - Haeb-Umbach, Reinhold; Ney, Hermann (IEEE Transactions on Speech and Audio Processing)
The authors describe the improvements in a time-synchronous beam search strategy for a 10000-word continuous-speech recognition task. Basically they introduced two measures, namely a tree organization of the pronunciation lexicon and a novel look-ahead technique at the phoneme level. The experimental tests performed showed that the number of state hypotheses could be reduced from 50000 to 3000, i.e., by a factor of about 17. At the same time, the word error rate did not increase.

Progress in Large-Vocabulary, Continuous Speech Recognition - Ney, Hermann; Steinbeiss, Volker; Aubert, Xavier L.; Haeb-Umbach, Reinhold (Artifical Intelligence, Progress and Prospects of Speech Research and Technology, Munich)

An Overview of the Philips Research System for Large Vocabulary Continuous Speech Recognition - Ney, Hermann; Steinbeiss, Volker; Haeb-Umbach, Reinhold; Tran, Bach Hiep (International Journal on Pattern Recognition and Artificial Intelligence)
This paper gives an overview of a research system for phoneme based, large vocabulary continuous speech recognition. The system to be described has been applied to the SPICOS task, the DARPA RM task and a 12000 word dictation task. Experimental results for these three tasks will be presented. Like many other systems, the recognition architecture is based on an integrated statistical approach. In this paper, we describe the characteristic features of the system as opposed to other systems: (1) The Viterbi criterion is consistently applied both in training and testing. (2) Continuous mixture densities are used without any tying or smoothing; this approach can be viewed as a sort of statistical template matching. (3) Time-synchronous beam search is used consistently throughout all tasks; extensions using a tree organization of the vocabulary and phoneme lookahead are presented so that a 12000 word task can be handled.

Synthesis for Off-line Testability - Hellebrand, Sybille; Juergensen, Arne; Wunderlich, Hans-Joachim

Chip Level Test Planning for Controlling the Tradeoff between Hardware Overhead and Test Time - Hellebrand, Sybille; Juergensen, Arne; Stroele, Albrecht; Wunderlich, Hans-Joachim

Effiziente Testsatzkodierung für Prüfpfad-basierte Selbsttestarchitekturen - Venkataraman, Srikanth; Rajski, Janusz; Hellebrand, Sybille; Tarnick, Steffen
Keywords: WORKSHOP

Ein Verfahren zur testfreundlichen Steuerwerkssynthese - Hellebrand, Sybille; Wunderlich, Hans-Joachim
Keywords: WORKSHOP

Synthesis for Testability - the ARCHIMEDES Approach - Hellebrand, Sybille; Paulo Teixeira, Joao; Wunderlich, Hans-Joachim
Keywords: WORKSHOP

Energetics and Structure of Ordered Sb Overlayers and Sb Clusters on GaAs(110) Probed by Ab Initio Calculations - Bechstedt, F; Schmidt, Wolf Gero; Wenzien, B (Europhysics Letters (EPL))

First principles calculations of interface phonons of an Epitaxial Sb monolayer on GaAs(110) and InP(110) - Schmidt, Wolf Gero; Srivastava, GP (Solid State Communications)

Pulsewidth modulation based on real-time solution of algebraic harmonic elimination equations - Sun, J.; Grotstollen, I. (Proceedings of IECON'94 - 20th Annual Conference of IEEE Industrial Electronics)

A new self-commissioning scheme for an asynchronous motor drive system - Ruff, M.; Bunte, A.; Grotstollen, H. (Proceedings of 1994 IEEE Industry Applications Society Annual Meeting)

DSP-based real-time harmonic elimination of PWM inverters - Sun, J.; Beineke, S.; Grotstollen, H. (Proceedings of 1994 Power Electronics Specialist Conference - PESC'94)

Modeling of high frequency inductors - Heinemann, L.; Schulze, R.; Wallmeier, P.; Grotstollen, H. (Proceedings of 1994 Power Electronics Specialist Conference - PESC'94)

Analysis and design of isolated high power boost topologies and simulations with quasi-static and quasi-stationary transformer models - Fröhleke, N.; Becker, B.; Grotstollen, H.; Magaritis, B.; Vollmer, L. (Proceedings of 1994 IEEE Industry Applications Society Annual Meeting)

Isolated boost full bridge topology suitable for high power and power factor correction - Fröhleke, N.; Mende, R.; Grotstollen, H.; Margaritis, B.; Vollmer, L. (Proceedings of IECON'94 - 20th Annual Conference of IEEE Industrial Electronics)

Computer aided optimization of multi-winding transformers for SMPS considering HF-effects - Fröhleke, N.; Becker, B.; Wallmeier, P.; Grotstollen, H. (Proceedings of 1994 IEEE Industry Applications Society Annual Meeting)

Erik Heijerman/H. Walter Schmitz (eds.), Significs, Mathematics and Semiotics. The Signific Movement in the Netherlands. Proceedings of the International Conference Bonn 19–21 November 1986. Nodus Publicationen: Münster 1991 (= Materialien zur Geschichte der Sprachwissenschaft und der Semiotik; 5) - Peckhaus, Volker (Modern Logic)

Alexander Rüstow's Thesis, Beitrag für russell-l@mcmail.cis.mcmaster am 17. Juni 1994 [Abdruck: Rüstow’s Thesis on Russell’s Paradox, History of Logic Newsletter, Nr. 13 (September–Oktober 1994), 2–3] [revidierte Fassung: Rüstow’s Thesis on Russell’s Paradox”, Modern Logic 5 (1995), 167–169] - Peckhaus, Volker
[Abdruck siehe 7.13, revidierte Fassung 4.18]

Betrieb der feldorientierten geregelten Asynchronmaschine im Bereich oberhalb der Nenndrehzahl - Josef Wiesing, Josef

[Art.] Kunstsoziologie - Süßmann, Johannes (Spezielle Soziologien. Problemfelder, Forschungsbereiche, Anwendungsorientierungen)

An Efficient Procedure for the Synthesis of Fast Self-Testable Controller Structures - Hellebrand, Sybille; Wunderlich, Hans-Joachim (ACM/IEEE International Conference on Computer-Aided Design (ICCAD'94))

Synthese schneller selbsttestbarer Steuerwerke - Hellebrand, Sybille; Wunderlich, Hans-Joachim (Tagungsband der GI/GME/ITG-Fachtagung & Rechnergestützter Entwurf und Architektur mikroelektronischer Systeme)

Synthesis of Self-Testable Controllers - Hellebrand, Sybille; Wunderlich, Hans-Joachim (European Design and Test Conference (EDAC/ETC/EUROASIC))

Michael Hamburgers Übersetzungen und einige neue Tendenzen in der englisch-sprachigen Hölderlin-Rezeption - van Laak, Lothar; Bartels, Kathrin; Brenig, Claudia; Prudlo, Marion (Hölderlin-Jahrbuch 29)

"In den Wald gehen, tief in den Wald hinein" Autoerotische Phantasmen männlicher Autorschaft in Thomas Bernhards Holzfällen. Eine Erregung - Öhlschläger, Claudia (AUTO(R)EROTIK. Gegenstandslose Liebe als literarisches Projekt)

Maskerade. Bericht über das 3. Symposium des Münchener Graduiertenkollegs Geschlechterdifferenz & Literatur. Ludwig- Maximilians-Universität München (27.-29.10.1994) - Öhlschläger, Claudia (Rundbrief Frauen in der Literaturwissenschaft 43: Postfeminismus. Dez. 1994)

"Weibsfauna". Zur Koinzidenz von Tiergeschichte und Pornographie am Beispiel von Bambi und Josefine Mutzenbacher - Öhlschläger, Claudia; Schmidt, Dietmar (Hofmannsthal-Jahrbuch 2)

A Doubly Branched Nonionic Oligooxyethylene V-Amphiphile: Effect of Molecular Geometry on Liquid-Crystalline Phase Behavior, 3 - Kratzat, Krystyna; Schmidt, Claudia; Finkelmann, Heino (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Sprachbiographie und Sprachstörung. Fallstudien zur Textproduktion bei hirnorganischen Erkrankungen

WAVELENGTH-SELECTIVE POLARIZATION ANALYZER WITH INTEGRATED TI LINBO3 ACOUSTOOPTICAL TE-TM CONVERTER - REHAGE, M; Noé, Reinhold (ELECTRONICS LETTERS)

Micromechanic Pressure Sensors with Optical Readout and CMOS-Amplifiers on Silicon - Hilleringmann, Ulrich; Adams, S.; Goser, K. (ESSDERC ’94: 24th European Solid State Device Research Conference)

Vertical transport studied by sub-picosecond four-wave mixing experiments - Meier, Torsten; Feldmann, J.; von Plessen, G.; Thomas, P.; Göbel, E.O.; Goosen, K.W.; Miller, D.A.B.; Cunningham, J.E. (Coherent Optical Interactions in Semiconductors)
Since the realization of semiconductor heterostructures vertical transport of electrically injected carriers has been one of the most interesting topics in semiconductor physics. Precise engineering of semiconductor layers and thus electronic energy levels allows the tailoring of transport properties over a wide range and has even led to the invention of semiconductor devices relying on ballistic electron transport. In addition, negative differential resistance (NDR) can be realized by using tunneling diodes containing double-barrier heterostructures or a superlattice structure.5,6 Actually, the proposal of Esaki and Tsu5 to use electronic Bloch oscillations in the miniband of a semiconductor superlattice to realize NDR marked the starting point for the physics and applications of semiconductor heterostructures.

Theory of polarization-dependent four-wave mixing using the optical Bloch equations - Meier, Torsten; Bennhardt, D.; Thomas, P.; Hu, Y.Z.; Binder, R.; Koch, S.W. (Coherent Optical Interactions in Semiconductors)
Transient four-wave mixing (TFWM) experiments have been widely used to study the excitation dynamics of excitons in quantum wells [1]. Recently is has been observed that TFWM signals, especially quantum beats between heavy-hole (hh) and light-hole (lh) excitons, strongly depend on the polarization of the incident laser pulses [2–6]. This dependence is presently being investigated.

Contributions of Bound and Unbound Two-Exciton States to the Nonlinear Optical Response of GaAs Quantum Wells - Meier, Torsten; Kuhl, J.; Mayer, E.J.; Smith, G.O.; Bennhardt, D.; Schulze, A.; Thomas, P.; Hey, R.; Ploog, K. (International Conference on Ultrafast Phenomena)
The strong influence of exciton/exciton interaction on the nonlinear optical response of the 2D exciton in GaAs quantum wells has been demonstrated in several recent experimental studies. The theoretical model for the microscopic coupling mechanism is still the subject of controversy, however. In ref. [1], we have presented a model including a density dependent coupling between opposite spin excitons which assumes that the interaction results in a renormalization of the matrix elements, dephasing rates and energies of the transition from the single-exciton state to the two-exciton state with respect to the corresponding quantities for the single exciton transitions. In contrast, Wang et al. claim that all experimental observations are explained by a density induced dephasing rate and that biexciton states play no role [2]. Here we present a new 3-pulse degenerate-four-wave-mixing (DFWM) configuration which is able to differentiate between pure local field effects and biexcitonic contributions to the time-integrated signal. Experiments were performed on an almost homogeneously broadened GaAs/Al0.3Ga0.7As single QW (well width 20 nm, photoluminescence line 0.3 meV, homogenous linewidth 0.15 meV) in the backward reflection geometry. The sample was cooled to 10 K and excited by a sequence of three pulses (1.1 ps duration) with equal intensity, wave vectors 𝑘→1,𝑘→2,𝑘→3 and delays τ12 and τ13 between the second and first and the third and first pulse, respectively. The signal was monitored in the direction 𝑘→𝑠=𝑘→1+𝑘→2−𝑘→3 which provides no signal for the chosen pulse length if local field and renormalization effects are negligible. The peak intensity of the time-integrated DFWM signal has been calculated by solving the optical Bloch for a system of two non-interacting two-level systems (2LS) with opposite circular polarization selection rules (local field effect) and for the renormalized four-level system (4LS) depicted in Fig. 1 which assumes the formation of biexcitons between excitons with opposite spins. The signal strength is proportional to the strength of the local field in the case of the 2LS and to the renormalization for the 4LS. The peak signal intensities expected for pure local field and pure biexction contributions are summarized in the second and third column of Table 1 for eight experimental configurations applying different linear and circularly polarized pulses. The values are normalized to the signal strength predicted for three parallel linearly polarized pulses. Close inspection of the data reveals remarkable differences of the peak amplitude with polarization geometry for the two coupling models.

Observation of Biexcitons in Time-Resolved Degenerate-Four-Wave-Mixing on GaAs Quantum Wells - Meier, Torsten; Mayer, E.J.; Smith, G.O.; Kuhl, J.; Bennhardt, D.; Schulze, A.; Thomas, P.; Hey, R.; Ploog, K. (International Conference on Ultrafast Phenomena)
Although the importance of exciton/exciton interactions for the nonlinear optical response of GaAs quantum wells (QW) is well established by many experimental observations, the role of biexciton states in these processes is still an open question, even at low excitation densities. Evidence for the formation of biexcitons has been independently derived from pump-probe studies [1], from the density dependence of the photoluminescence (PL) line shape [2] and from signal modulations observed in degenerate-four-wave-mixing (DFWM) with incoherent light pulses [3]. Here, we report on time-resolved DFWM with parallel (PP) and cross-polarized (CP) pulses. Depending on the polarization geometry, the signals reveal strong quantum beats which correspond to the splitting between either the heavy hole (hh) and light hole (lh) exciton or the hh exciton and the biexciton.

Interplay Between Inhomogeneous Broadening and Coulomb Interaction in the Dynamics of Excitonic Wave Packets - Meier, Torsten; Koch, M.; Jahnke, F.; Feldmann, J.; Schäfer, W.; Thomas, P.; Koch, S.W.; Göbel, E.O.; Nickel, H.
A proper description of subpicosecond four-wave-mixing (FWM) experiments for excitonic transitions in semiconductor heterostructures must consider the fact that the spectrally broad laser pulses excite not only the 1s bound exciton state but also energetically higher bound exciton states and the lower-lying part of the unbound continuum states. In this paper, we report results of transient and time-resolved FWM-experiments in which such ’excitonic wave packets’ play a crucial role. In addition, a theoretical treatment of the problem based on the solution of the semiconductor Bloch is presented. We show that the time-dependent nonlinear response is determined by an interplay between inhomogeneous broadening and Coulomb interaction.

Kreativität und Reproduktion. Annäherung an den Bildungshorizont von Ursula Weida - Schuster, Britt-Marie (Bausteine zu einer Geschichte des weiblichen Sprachgebrauchs. Forschungsberichte – Projektangebote – Forschungskontexte)
Keywords: Sprachliche Formelhaftigkeit/-Musterhaftigkeit

Die Artes liberales im frühen Mittelalter (5.-9. Jh.). Das Quadrivium und der Komputus als Indikatoren für Kontinuität und Erneuerung der exakten Wissenschaften zwischen Antike und Mittelalter - Englisch, Brigitte

Problem Independent Distributed Simulated Annealing and its Applications - Diekmann, Ralf; Simon, Jens (Applied Simulated Annealing)

Parallel Architectures and Their Efficient Use

Richard Beer-Hofmann (1866-1945). Studien zu seinem Werk

Stanislaw Przybyszewski: Schnee und andere Dramen (Edition) - Eke, Norbert Otto

Nikolaus Lenau. Werke und Briefe. Historisch-kritische Gesamtausgabe. Bd. 7. Aufzeichnungen. Vermischte Schriften. Text und Kommentar (Edition) - Eke, Norbert Otto; Oellers, Norbert; Skrodzki, Karl Jürgen; Steinecke, Hartmut

Rettung des Sinns. Jaákobs Traum und das Projekt einer Geschichtstheodizee - Eke, Norbert Otto (Richard Beer-Hofmann (1866-1945). Studien zu seinem Werk)

Richard Beer-Hofmann – Zur Einführung - Eke, Norbert Otto; Helmes, Günter (Richard Beer-Hofmann (1866-1945). Studien zu seinem Werk)

„Freiheit ist nur in dem Reich der Träume“. Revolutionsprojektionen deutscher Dramen nach 1789. Ein historischer Aufriß (mit einem Ausblick bis zum Nachmärz) - Eke, Norbert Otto (Grabbe Jahrbuch 12)

Eine Gesamtbibliographie des deutschen Romans 1815-1830. Anmerkungen zum Problemfeld von Bibliographie und Historiographie - Eke, Norbert Otto (Zeitschrift für Germanistik)

„Deutschland ortlos“. Dekonstruktionen des Nationalen bei Heiner Müller - Eke, Norbert Otto (Dichter und ihre Nation)

Calculating the Influence of Skylight-Polarization on the Transmission of Encapsulations of PV-Modules - Krauter, Stefan; Hanitsch, Rolf (Proceedings of the Cairo International Conference of Renewable Energy Sources, Kairo (Ägypten), 30. Dezember 1992 – 2. Januar 1993)